Neuropathology in Mice Expressing Mouse Alpha-Synuclein - DEV, KUMLESH (PLoS, 2011)
?-Synuclein (?SN) in human is tightly linked both neuropathologically and genetically to Parkinson's disease (PD) and related disorders. Disease-causing properties in vivo of the wildtype mouse ortholog (m?SN), which carries a threonine at position 53 like the A53T human mutant version that is genetically linked to PD, were never reported. To this end we generated mouse lines that express m?SN in central neurons at levels reaching up to six-fold compared to endogenous m?SN. Unlike transgenic mice expressing human wildtype or mutant forms of ?SN, these m?SN transgenic mice showed pronounced ubiquitin immunopathology in spinal cord and brainstem. Isoelectric separation of m?SN species revealed multiple isoforms including two Ser129-phosphorylated species in the most severely affected brain regions. Neuronal Ser129-phosphorylated ?SN occured in granular and small fibrillar aggregates and pathological staining patterns in neurites occasionally revealed a striking ladder of small alternating segments staining either for Ser129-phosphorylated ?SN or ubiquitin but not both. Axonal degeneration in long white matter tracts of the spinal cord, with breakdown of myelin sheaths and degeneration of neuromuscular junctions with loss of integrity of the presynaptic neurofilament network in m?SN transgenic mice, was similar to what we have reported for mice expressing human ?SN wildtype or mutant forms. In hippocampal neurons, the m?SN protein accumulated and was phosphorylated but these neurons showed no ubiquitin immunopathology. In contrast to the early-onset motor abnormalities and muscle weakness observed in mice expressing human ?SN, m?SN transgenic mice displayed only end-stage phenotypic alterations that manifested alongside with neuropathology. Altogether these findings show that increased levels of wildtype m?SN does not induce early-onset behavior changes, but drives end-stage pathophysiological changes in murine neurons that are strikingly similar to those evoked by expression of human wildtype or mutant forms.
PUBLISHED
Keywords: Neuroscience; Parkinson's Disease